(untitled) (Международный научный журнал «Инженер», 2026)
The article defines the methods of strengthening the embankment with reinforced concrete piles in the area of the interface of the roadbed with the shore supports of the bridge using theoretical mathematical expressions in accordance with different heights of the embankment. Calculations were performed based on seismograms recorded by CM-3 sensors during experimental studies of the amplitude, frequency, oscillation period, and logarithmic decrement of the soil of the roadbed as a result of strengthening the embankment with reinforced concrete piles at the approaches to the bridges. In addition, the amplitude-frequency characteristics of vibrations and displacements near the pile and at the edge of the roadbed during vibrations are determined.